Online Contents / Gemeinsamer Bibliotheksverbund - Gemeinsamer Bibliotheksverbund (1993)
The database Online Contents - South Asia is a selection of bibliographic data from the Swets database Online Contents which is enlarged regularly by additional data provided by the Library of the South Asia Institute Heidelberg.